Cricket mix optimization using heuristic framework after ensuring Markovian equilibrium - Ray, S.; Roychowdhury, S. (Journal of Sports Analytics, 2021)
International Cricket Council, in consultation with its member boards, prepares the Future Tours and Programme (FTP) which is an eight year long itinerary covering world championships in three formats of cricket, bilateral series and other tournaments. However, the FTP (2015-2023) had been criticized for its asymmetric itinerary and the point system for World Test championship and the FTP (2023-2031) is being criticized for including eight championships in limited formats and enhanced workload for players. Cricket mix standardization like marketing and product mix can work in homogeneous markets. This study derives three homogeneous markets of four teams each using hierarchical cluster analysis. For each market, it finds out the Markovian equilibrium analyzing cricket mix transition over past years. While the same can be used to derive the number of games per format per country, the study proposes a heuristic approach for fine tuning the same taking care of major stakeholders` (e.g. Administrators, Players and Spectators) aspirations. Despite scores of criticisms and articles on the issue, there is hardly any scholastic contribution on game scheduling in the extant literature. This study thus is a pioneering effort in helping the policy makers to create a balance between cricket formats within each homogeneous market.